Teacher Education in Asia : A Regional Survey - Philippines Univ., Quezon City. Asian Inst. for Teacher Educators; Philippines Univ., Quezon City. Asian Inst. for Teacher Educators (Washington, D.C. : Distributed by ERIC Clearinghouse, 1972)
This survey is limited to the status of teacher education in Asia only as it pertains to the training of primary and general secondary school teachers. The programs of 19 countries are reviewed. Attention is given to policies of admission and enrollment, student aid, facilities, curriculum, qualifications of educators, in-service education, and research. A selected bibliography is included. (JA)
Sponsoring Agency: United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and Oceania.
Microfiche.
Keywords: Educational Research; Elementary School Teachers; Foreign Countries; Program Evaluation; School Surveys; Secondary School Teachers; Surveys; Teacher Education; Teacher Education Curriculum; Teacher Education Programs